Efektivitas Pendidikan Kristiani Anak bagi Pertumbuhan Jemaat - Raymond J. Dumbi; Daniel C. Kambey; Marde C.S. Mawikere (Peneliti.net, 2021)
The purpose of the research is to Analyse the Effectiveness of Children’s Christian Education for Congregational Growth. Children’s Christian Education is pivotal in church services for the reason it will make an impact on congregational growth both in quality and quantity. The research is qualitative research, the subject is the church pastor, children and parents’ minister. Data are collected through observation, interviews, and documentation studies. The results showed that there were three models of Children’s Education, namely Sunday School, Children’s Worship Service. The factors inhibiting the effectiveness of the internal factor are children’s minister shortage, lack of means of transportation and the infrastructure is inadequate. Whilst externally, the factors are the church is not accepted by the society altogether and the Covid-19 Pandemic. This research is expected to provide broaden awareness to Church Pastors and Children’s Ministers who are involved in Children’s Christian Education and churches in an endeavour to enhance the effectiveness of children’s Christian education for congregational growth